Intraoperative changes in blood lactate levels are associated with worse short-term outcomes after cardiac surgery with cardiopulmonary bypass. (November 2019) - Duval, Benoit; Besnard, Thibaud; Mion, Stefano; Leuillet, Sébastien; Jecker, Olivier; Labrousse, Louis; Rémy, Alain; Zaouter, Cedrick; Ouattara, Alexandre
Background: A high perioperative blood lactate level has been reported to be associated with poor outcomes after cardiac surgery. More than isolated peaks of lactate values, it should be more interesting to take into account changes in intraoperative blood lactate level (∆Lact). This large-scale retrospective study evaluated the relationship between ∆Lact and overall intensive care unit morbidity and 30-day all-cause mortality. Methods: Perioperative data from consecutive patients undergoing on-pump cardiac surgery between September 2010 and June 2016 were retrospectively analysed through our institutional database including clinical, transfusion and laboratory test results implemented prospectively by physicians. Blood lactate levels were initially measured after induction of anaesthesia (baseline) and periodically during the surgery. The ∆Lact was defined as the difference between the highest intraoperative blood lactate and the baseline lactate level and offered the opportunity to stratify patients into four subgroups: ⩽0, 0.1-0.9, 1-1.9 and ⩾2 mmol L −1 . Results: From the 7, 795 patients found eligible during the study period, 7, 447 patients were analysed. The median ∆Lact of our patients was 0.6 (0.3-1) mmol L −1 . Most of the studied patients (65.9%) exhibited a ∆Lact between 0.1 and 0.9 mmol L −1 . A concentration-dependent relationship was observed between ∆Lact and intensive care unit morbidity and 30-day mortality. After adjustment for co-variables, all ∆Lact > 0 was associated with an increase in overall intensive care unit morbidity. An independent relationship was also found between ∆Lact and 30-day mortality as of a 1 mmol L −1 increase. Conclusion: Our results suggest that ∆Lact is associated with poor short-term outcomes in adult cardiac surgical patients.